Isolation and identification of a novel erythromycin-degrading fungus, Curvularia sp. RJJ-5, and its degradation pathway. Issue 1 (18th December 2020) - Ren, Jianjun; Deng, Liujie; Niu, Dongze; Wang, Zhenzhu; Fan, Bo; Taoli, Huhe; Li, Zhijie; Zhang, Jin; Li, Chunyu
ABSTRACT: Erythromycin pollution is an important risk to the ecosystem and human health worldwide. Thus, it is urgent to develop effective approaches to decontaminate erythromycin. In this study, we successfully isolated a novel erythromycin-degrading fungus from an erythromycin-contaminated site. The erythromycin biodegradation characteristics were investigated in mineral salt medium with erythromycin as the sole carbon and energy source. The metabolites of erythromycin degraded by fungus were identified and used to derive the degradation pathway. Based on morphological and phylogenetic analyses, the isolated strain was named Curvularia sp. RJJ-5 (MN759651). Optimal degradation conditions for strain RJJ-5 were 30°C, and pH 6.0 with 100 mg L −1 erythromycin substrate. The strain could degrade 75.69% erythromycin under this condition. The following metabolites were detected: 3-depyranosyloxy erythromycin A, 7, 12-dyhydroxy-6-deoxyerythronolide B, 2, 4, 6, 8, 10, 12-hexamethyl-3, 5, 6, 11, 12, 13-hexahydroxy-9-ketopentadecanoic acid and cladinose. It was deduced that the erythromycin A was degraded to 3-depyranosyloxy erythromycin A by glycoside hydrolase in the initial reaction. These results imply that Curvularia sp. RJJ-5 is a novel erythromycin-degrading fungus that can hydrolyze erythromycin using a glycoside hydrolase and has great potential for removing erythromycin from mycelial dreg and the contaminated environment. Abstract : A novel erythromycin-degrading fungus Curvularia sp. RJJ-5 that was isolated and could degrade 75.69% of erythromycin after 96 h has potential for treatment of erythromycin mycelial dreg and the contaminated environment.